A GOOD LIFE? CRITICAL FEMINIST APPROACHES TO INFLUENCER ECOLOGIES - Glatt, Zoë; Banet-Weiser, Sarah; Bishop, Sophie; Sobande, Francesca; Wissinger, Elizabeth; Entwistle, Joanne; Duffy, Brooke Erin; Rocamora, Agnès; Arriagada, Arturo (AoIR Selected Papers of Internet Research, 2020)
Social media platforms are widely lauded as bastions for entrepreneurial self-actualisation and creative autonomy, offering an answer to historically exclusive and hierarchical creative industries as routes to employability and success. Social media influencers are envied by audiences as having achieved ‘the good life’, one in which they are able to ‘do what they love’ for a living (Duffy 2017). Despite this ostensive accessibility and relatability, today’s high-profile influencer culture continues to be shaped by ‘preexisting gendered and racial scripts and their attendant grammars of exclusion’ as Sarah Banet-Weiser (2012) argued in the early days of socially mediated entrepreneurship (p. 89; see also Bishop, 2017). In Western contexts only a narrow subset of white, cis-gender, and heterosexual YouTubers, Instagrammers, TikTokers, and Twitch streamers tend to achieve visibility as social media star-creators, and celebratory discourses of diversity and fairness mask problematic structures that exclude marginalized identities from opportunities to attain success. A key aim of this panel is thus to draw attention to marginalized creator communities and subjectivities, including women, non-white, and queer creators, all of whom face higher barriers to entry and success. More broadly, by taking seriously both the practices and discourses of social media influencers, the panellists aim to challenge popular denigrations of influencers as vapid, frivolous, or eager to freeload. We locate such critiques in longstanding dismissals of feminized cultural production (Levine, 2013) and argue, instead, that we need to take seriously the role of influencers in various social, economic, and political configurations.